Valuing environmental goods and services (EGS) of the mangrove in artisanal oyster farming: Las Tunas, Cuba - Betanzos-Vega, Abel; Tripp-Quezada, Arturo; Macías-Aguilera, Esnoldo; Leyva-Segura, Adalberto; Arencibia-Carballo, Gustavo; Mazón-Suástegui, José Manuel (Ecosistemas y Recursos Agropecuarios, 2022)
In Cuba, the production of mangrove oyster Crassostrea rhizophorae comes from extractive ﬁshing (75%) and artisanal cultivation (25%). In extractive ﬁshing, the barking or cutting of the roots of the red mangrove (Rhizophora mangle) occurs during the collection of oysters. In cultivation, mangrove trunks and branches are used for farms and for making collectors, which damages the ecosystem and reduces the supply of environmental goods and services (BSA) provided by the mangrove. With the objective of evaluating through a cost-beneﬁt analysis the oyster farming activity in Puerto Padre, Las Tunas, Cuba, and determining the economic and environmental viability of artisanal oyster farming, productive strategies with an ecosystemic approach were applied, including an ecological value representative of the beneﬁt gross of mangrove functions. Artisanal farming turned out to be an economically and environmentally viable production alternative, which allowed a higher average yield in oyster meat (6.4%), versus meat yield from extractive ﬁshing (5.8%). The inclusion, in the cost-beneﬁt analysis of the oyster farming activity, of the cost for damages and beneﬁts to the mangrove swamp, indicates the need to include the BSA valuation in the traditional mechanisms of economic evaluation.